Frondoside A induces AIF-associated caspase-independent apoptosis in Burkitt lymphoma cells. Issue 12 (2nd December 2017) - Dyshlovoy, Sergey A.; Rast, Stefanie; Hauschild, Jessica; Otte, Katharina; Alsdorf, Winfried H.; Madanchi, Ramin; Kalinin, Vladimir I.; Silchenko, Alexandra S.; Avilov, Sergey A.; Dierlamm, Judith; Honecker, Friedemann; Stonik, Valentin A.; et al.
Abstract: For patients with refractory or relapsed Burkitt lymphoma (BL), no standard therapy is available for second-line treatment to date. Nonfunctional caspases-dependent apoptosis pathways, inactivating p53 mutations and pro-survival autophagy prevent activity of conventional chemotherapy. Thus, new drugs bypassing these mechanisms of resistance are required. Here, we investigated the efficacy of the marine natural compound frondoside A (FrA) in eight BL cell lines. FrA revealed cytotoxic effects in all cell lines tested including the multiresistant CA46 cells. Remarkably, FrA induced caspases- and p53-independent apoptosis, which was characterized by decreased expression of antiapoptotic survivin and Bcl-2, mitochondria targeting (release of cytochrome C, HtrA2/Omi and the apoptosis-inducing factor (AIF), and altered production of ROS) and translocation of AIF to the nuclei. In addition, signs of inhibition of pro-survival autophagy were observed. Thus, FrA is a promising candidate for the treatment of refractory or relapsed BL revealing resistances to standard therapies.